(untitled) (European Journal of Child Development, Education and Psychopathology, 2021)
Body dissatisfaction (BD) is an important predictor of risky eating behaviors (REB), although BD commonly presents with symptoms of anxiety, it is unknown if this moderates the relationship between BD and REB in the adolescent population. Objective: to analyze the moderating effect of anxiety symptoms in the relationship between BD and REB. Method: Explanatory cross-sectional study. Non-probabilistic sampling n = 500 female adolescents in school, ages between 14 and 19 years old (M = 16.81, SD = 1.33). The participants answered the Eating Attitudes Test-26, Body Shape Questionnaire-8D and Hospital Anxiety and Depression Scale. Informed consent was obtained from parents and informed consent from participants. Results: anxiety symptoms moderated the relationship between BD and REB, a stronger association in high levels of anxiety (b = .51, p <.001) than in low levels (b = .32, p <.001). Post-hoc analysis showed that the slopes of high vs low anxiety symptoms were significantly different (t = 2.90; p <.001). Discussion: Anxiety moderates the relationship of two predictors of eating disorders, influencing the increased risk of developing them. Practical implications at the level of prevention and treatment of eating disorders are discussed.